Which stocks are driven by which interest rates?: Evidence from listed real estate. Issue 3 (3rd July 2021) - Weis, Christian; Woltering, René-Ojas; Sebastian, Steffen
ABSTRACT: This paper analyzes the return sensitivities of real estate value and growth stocks to changes in five different interest rate proxies. Using a global sample of 352 listed real estate companies from 12 countries as a test object, we find that real estate value stocks are more sensitive than real estate growth stocks to changes in the short-term interest rate. This finding is consistent with the theory that investors with shorter investment horizons trade off the high initial yield of value stocks against lower-risk short-term interest rates. In contrast, real estate growth stocks are more sensitive to changes in the long-term interest rate, which is consistent with a stronger impact on the present value of the future cash flows of growth stocks. We also find that real estate value stocks are more sensitive to changes in the credit yield. Because credit costs have a direct impact on a firm's cost of capital, this result is consistent with risk-based theories of the value premium, which argue value stocks are riskier because they tend to have higher leverage and greater default probability.